2017
DOI: 10.1080/00498254.2016.1275881
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of caspase-8 and -9 to liver injury from CYP2E1-produced metabolites of halogenated hydrocarbons

Abstract: 1. Drug-induced liver injury is difficult to predict at the pre-clinical stage. This study aimed to clarify the roles of caspase-8 and -9 in CYP2E1 metabolite-induced liver injury in both rats and cell cultures in vitro treated with carbon tetrachloride (CCl), halothane or sevoflurane. The human hepatocarcinoma functional liver cell line was maintained in 3-dimensional culture alone or in co-culture with human acute monocytic leukemia cells. 2. In vivo, laboratory indices of liver dysfunction and histology wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…As a typical traditional Chinese medicine, AST has been widely used for anti-inflammatory treatment (Hsieh, Liu, Chen, Huang, & Wu, 2020;Xie et al, 2020;Zhang et al, 2020). Our study indicated (Ijiri et al, 2018). Caspase-3 is one of the major executioners of apoptosis (Langford, McGee, Ta, Redens, & Texada, 2011).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…As a typical traditional Chinese medicine, AST has been widely used for anti-inflammatory treatment (Hsieh, Liu, Chen, Huang, & Wu, 2020;Xie et al, 2020;Zhang et al, 2020). Our study indicated (Ijiri et al, 2018). Caspase-3 is one of the major executioners of apoptosis (Langford, McGee, Ta, Redens, & Texada, 2011).…”
Section: Discussionmentioning
confidence: 52%
“…Multiple signal transmitting pathways act collectively with caspases to induce apoptosis. Particularly, caspase‐9 is an initiator caspase participating in mitochondrial apoptosis and other apoptosis pathways (Ijiri et al., 2018). Caspase‐3 is one of the major executioners of apoptosis (Langford, McGee, Ta, Redens, & Texada, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of these caspases is a biochemical marker of apoptosis. 26 Apoptosis has been defined as a type of programmed cell death, 27 which proceeds through two classical signal transduction pathways: the external and internal pathways. 28 The external pathway is mediated by caspase‐8, whereas the internal pathway is triggered by caspase‐9.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of these caspases is a biochemical marker of apoptosis [25]. Apoptosis has been de ned as a type of programmed cell death [26], which proceeds through two classical signal transduction pathways: the external and internal pathways [27]. The external pathway is mediated by caspase-8, whereas the internal pathway is triggered by caspase-9.…”
Section: Discussionmentioning
confidence: 99%